Enhancing SARS-CoV-2 DNA Vaccines with CD40 Ligand and Lipid Nanoparticle Delivery - Tamming, Levi Andrew (Université d'Ottawa | University of Ottawa, 2026)
Despite widespread vaccination, SARS-CoV-2 continues to circulate globally, with ongoing transmission driven by the emergence of immune-evasive variants and the waning of infection- and vaccine-induced immunity. Although mRNA vaccines induce strong early responses, serum neutralizing antibody (NAb) titers often wane substantially within 7–9 months post-vaccination, increasing susceptibility to breakthrough infection. While updated, variant-matched boosters can restore higher levels of protection, their overall impact is constrained by declining uptake, rollout timelines that can leave vaccines mismatched to circulating variants, and immune imprinting. Novel vaccination strategies are needed to elicit more durable and broadly protective immunity. Multiple DNA vaccines against SARS-CoV-2 have been evaluated clinically, but most elicited only modest immune responses and often required specialized delivery systems. This thesis investigates two complementary approaches to enhance DNA vaccine performance against SARS-CoV-2: incorporation of CD40 ligand (CD40L) as a molecular adjuvant and formulation of DNA in ionizable lipid nanoparticles (DNA-LNPs). Fusing CD40L to the SARS-CoV-2 Spike enhanced the magnitude and breadth of humoral responses elicited by DNA, DNA-LNP and mRNA-LNP vaccines, while preferentially promoting Th1-skewed immunity. Encapsulation of DNA in LNPs markedly increased immunogenicity and broadened NAb activity, enabling neutralization and protection against both matched Delta and heterologous Omicron variants. This thesis also demonstrates that DNA-LNPs can afford long-term protective immunity, with durability of humoral immune response greatly exceeding those of mRNA-LNP vaccines six-months post-vaccination. Together, these findings support the feasibility and complementarity of CD40L adjuvants and LNP delivery to improve the potency, breadth, and durability of DNA vaccine-induced immunity, potentially reducing the need for frequent boosting.
Keywords: Vaccine; COVID-19; SARS-CoV-2; Antibody; Immunity; mRNA; Nanoparticle